Artificial Intelligence Readiness for Halal SMEs: The Role of Digital Capability, Halal Awareness, and Innovation Orientation - Salma Isfihany; Bella Laila Rahmah (Global Writing Academica Researching and Publishing, 2026)
This study examines the readiness of Halal Small and Medium-sized Enterprises (SMEs) to adopt Artificial Intelligence (AI) by synthesizing the existing body of knowledge on the roles of digital capability, halal awareness, and innovation orientation. The rapid advancement of AI technologies has created significant opportunities for enhancing operational efficiency, decision-making quality, and sustainable competitiveness within the halal business ecosystem. However, the successful implementation of AI requires organizational readiness that extends beyond technological infrastructure to include strategic, cultural, and knowledge-based capabilities. This study employs a literature review approach to systematically analyze and integrate relevant scholarly publications concerning AI readiness and its determinants in the context of Halal SMEs. The reviewed literature was critically examined to identify recurring themes, conceptual relationships, and emerging research trends associated with AI adoption in halal-oriented enterprises. The findings indicate that digital capability provides the technological foundation necessary for AI integration, while halal awareness strengthens organizational commitment to maintaining Sharia-compliant business practices during digital transformation. Furthermore, innovation orientation encourages organizational adaptability and supports the continuous exploration of AI-enabled business opportunities in increasingly dynamic markets. The synthesis also reveals that the interaction among these three dimensions forms a comprehensive framework that enhances the strategic readiness of Halal SMEs to embrace AI-driven transformation. This study contributes to the literature by offering an integrated conceptual perspective that bridges technological capability, halal values, and innovation-oriented organizational behavior within the AI readiness discourse. The proposed framework provides valuable theoretical insights for future research and practical guidance for policymakers, industry practitioners, and Halal SMEs seeking to accelerate AI adoption while preserving the principles of the halal ecosystem.